Transitions in the meaning of belonging: the struggle for enhanced access to resources among Palestinian-Arab women in Israel. Issue 9 (4th July 2022) - Meler, Tal; Benjamin, Orly
ABSTRACT : Discussions of the relatively low rate of labor market participation of Palestinian-Arab women in Israel often underline social control as compelling women to find employment in their residence area. Such discussions tend to assume women's cooperation with their communities without taking into account the range of possible negotiated positions which women take in order to enhance access to resources in the complex context of institutional racism, narrow opportunity base, and social control. Here we direct attention to Palestinian-Arab women with higher education, asking how they negotiate their belonging to different circles. We apply three theoretical processes of negotiating belonging proposed by Anthias. Each of these struggles presents specific barriers to women's occupations and their willingness to break gender, spatial, and occupational boundaries, increase their accessibility to employment opportunities in pursuit of quality jobs, establish financial independence, and evade social control in the communities of origin or remain dependent on it.